CONTRIBUTION OF A PAINTING ARTIST TO TURKISH EDUCATION HISTORY NAZMI ZIYA GÜRAN AND HIS ASSIGNMENT FOR SUPPLYING TEACHING MATERIAL - Meltem Begüm SAATÇI ATA (Fırat University, 2021)
Nazmi Ziya Güran (1881-September 11, 1937) is an artist who is one of the pioneers of the Impressionist movement in art in Turkey during the last years of the Ottoman Empire and the foundation days of the Republic of Turkey. He worked in the State service with painting art studies. Besides having an important place with his artistic works in the Turkish history he assumed important duties in matters concerning the Turkish education history. He worked at different levels of education system, as a teacher, director and inspector. Apart from this he also did works in which he carried out the art of painting and administration duties together. The subject of this article is one of these works which is about supply of course materials. Nazmi Ziya was assigned to supply course materials from Germany on behalf of the Ottoman Ministry of Education for 11 months between 1915 and 1916 that was during the First World War. The purpose of this study is to put forth the reasons of the assignment of Nazmi Ziya by the Ottoman Ministry of Education for the supply of teaching materials such as historical tables, geography plates to be used in the schools and to explain in detail his practices, preferences and their reasons in the process of his assignment in Germany. The main guiding sources of this study are the Ottoman archival documents and the articles written by Nazmi Ziya himself. These documents and articles also the other research papers are evaluated in accordance with the method of historical research. And it is understood that in this assignment Nazmi Ziya acted as an artist, educator and bureaucrat and he dealt with the subject of supplying these teaching material with the terms of art, education as well as its economic dimension. He fulfilled his task with the benefit of society and state in accordance with the national understanding of art. The results of his mission were evaluated by the Ottoman Ministry of Education and these teaching materials were used in the schools immediately.